Effect of Stone Size and Composition on Ultrasonic Propulsion Ex Vivo - Janssen, Karmon M. (Urology, 2017)
OBJECTIVE: To evaluate in more detail the effectiveness of a new designed more efficient ultrasonic propulsion for large stones and specific stone compositions in a tissue phantom model. In the first clinical trial of noninvasive ultrasonic propulsion, urinary stones of unknown compositions and sizes up to 10 mm were successfully repositioned. MATERIALS AND METHODS: The study included 8- to 12-mm stones of 4 different primary compositions (calcium oxalate monohydrate, ammonium acid urate, calcium phosphate, and struvite) and a renal calyx phantom consisting of a 12 mm × 30 mm well in a 10-cm block of tissue-mimicking material. Primary outcome was the number of times a stone was expelled over 10 attempts, with ultrasonic propulsion burst duration varying from 0.5 seconds to 5 seconds. RESULTS: Overall success rate at expelling stones was 95%. All calcium oxalate monohydrate and ammonium acid urate stones were expelled 100% of the time. The largest stone (12 mm) became lodged within the 12-mm phantom calyx 25% of the time regardless of the burst duration. With the 0.5-second burst, there was insufficient energy to expel the heaviest stone (0.88 g), but there was sufficient energy at the longer burst durations. CONCLUSION: With a single burst, ultrasonic propulsion successfully moved most stones at least 3 cm and, regardless of size or composition, expelled them from the calyx. Ultrasonic propulsion is limited to the stones smaller than the calyceal space, and for each burst duration, related to maximum stone mass.